PRINSIP ITIKAD BAIK DALAM LEMBAGA RECHTSVERWERKING PADA SISTEM AGRARIA INDONESIA - Mufarrijul Ikhwan; Munaddhimatus Silmi; Putri Kinanthi Dhayaning Bumi (RechtIdee, 2022)
Rechtsverwerking, term of customary law adopted in agrarian law, means losing land rights have been cultivated by other people on basis of good faith. This event can cause legal uncertainty and losses for other parties. This study aims to analyze the principle of good faith in rechtsverwerking in agrarian law, using a statutory and conceptual approach. Based on the analysis, it was found the principle of good faith in rechtsverwerking can be applied to land tenure for a minimum of twenty years and no one has filed a lawsuit for five years after  registration at the Land Office. This regulation has consequences for people who previously used the land but were abandoned, then done by other people and the previous land ruler did not carry out certain legal actions, their land rights could potentially be lost. Legal certainty is the purpose of regulation, but it cannot be denied that justice and expediency are also legal goals. So, someone who obtains rights based on rechtsverwerking needs to heed the principle of good faith and the acquisition of his rights does not harm the previous cultivator.